Organisatoriese doeltreffendheid in Suid-Afrika en Japan - H. J.J. Spoelstra (South African Journal of Business Management, 1981)
Organizational effectiveness in South Africa and Japan. Japan's extraordinary economic success of the past century makes it an excellent source of comparison with South Africa where economic success is still hampered by problems such as low productivity, unemployment and organizational ineffectiveness. In Japan the principles of utilization of manpower are based on the high priority given to labour as a factor of production. The life-time employment system, life-time training and seniority as motive for promotion and remuneration are examples of labour deployment. Decisions are initiated at the lowest levels and only arrived at by consensus while the only role of management is to maintain harmony during the process. Individual work input is high and labour unions play an important and supportive role in the effective functioning of organizations. Die besondere sukses van die Japanse ekonomie gedurende die afgelope eeu maak die land 'n uitstekende bron van vergelyking met Suid-Afrika waar ekonomiese sukses nog relatief laag is as gevolg van probleme soos lae produktiwiteit, werkloosheid en organisatoriese doeltreffendheid. In Japan word arbeidsbenuttingsbeginsels gefundeer in die besondere prioriteit wat aan arbeid as produksiefaktor toegeskryf word. Lewenslange indiensneming, lewenslange opleiding en die senioriteitsbeginsel by bevordering en vergoeding is voorbeelde van die benutting van arbeid. Besluite word op die laagste vlakke geinisieer en slegs deur konsensus bereik. Bestuur sien slegs toe dat harmonie in die proses gehandhaaf word. lndividuele werkinset is hoog en vakbonde speel 'n belangrike en ondersteunende rol in die doeltreffende funksionering van organisasies.